2012
DOI: 10.1111/j.1463-1318.2011.02760.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidental focal colonic lesions found on 18Fluorodeoxyglucose positron emission tomography/computed tomography scan: further support for a national guideline on definitive management

Abstract: Incidental abnormal colonic uptake of (18)FDG, determined by a PET/CT scan requires definitive colonic investigation in patients suitable for further treatment because significant colonic pathology is frequently identified. The benefit of this approach should be discussed in specialist MDT meetings and tailored to each patient; however, national guidelines for management are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…1,6,7,14,17 However, the present authors and others have shown the ability of PET to detect smaller adenomas, possibly due to more advanced histology (e.g., villous component or highgrade dysplasia) possibly due to greater metabolic activity. 9,12,14,22 Others report incidental detection of adenomas as small as 3e5 mm with high-grade dysplasia. 12 The present data once again challenge the concept that size is the only variable explaining adenoma detection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…1,6,7,14,17 However, the present authors and others have shown the ability of PET to detect smaller adenomas, possibly due to more advanced histology (e.g., villous component or highgrade dysplasia) possibly due to greater metabolic activity. 9,12,14,22 Others report incidental detection of adenomas as small as 3e5 mm with high-grade dysplasia. 12 The present data once again challenge the concept that size is the only variable explaining adenoma detection.…”
Section: Discussionmentioning
confidence: 97%
“…9,12,14,22 Others report incidental detection of adenomas as small as 3e5 mm with high-grade dysplasia. 12 The present data once again challenge the concept that size is the only variable explaining adenoma detection. In another well-performed, large study, Ravizza et al 22 found by multiand univariate analyses that a villous component and highgrade dysplasia were independently associated with PET positivity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We congratulate Farquharson et al. [1] for presenting an interesting and well‐designed study with a thoughtful discussion. A large volume of work has been required in following up a cohort incidentally found to have focal colorectal fluorodeoxyglucose (FDG) uptake in the course of undergoing positron emission tomography/computed tomography (PET/CT).…”
mentioning
confidence: 98%
“…The suggestion of guidelines for this situation seems excessive, however. After all, these cases are uncommon (24 in a single‐centre study over 26 months [1], equating to approximately one case per month). It would be a grave indictment of oncologists that they cannot provide adequate follow‐up for these particular cases.…”
mentioning
confidence: 99%